1990
DOI: 10.1007/bf02238843
|View full text |Cite
|
Sign up to set email alerts
|

Congenital polyvalvular disease in trisomy 18: Echocardiographic diagnosis

Abstract: Congenital heart disease is known to occur in greater than 90% of patients with trisomy 18, with ventricular septal defect and patent ductus arteriosus being the most frequently encountered lesions. The presence of congenital polyvalvular disease in trisomy 18 as assessed by pathological specimens has also been noted. Echocardiograms were obtained in 15 patients with trisomy 18 and in 12 infants with dysmorphic features, who did not have chromosomal abnormalities, in order to obtain an echocardiographic assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 17 publications
4
21
0
1
Order By: Relevance
“…Our findings are consistent with those of postnatal échocardio graphie studies in affected neonates and post mortem studies of stillbirths or postnatal deaths (table 2) [1][2][3][4]. The frequency of septal defects (84%) was higher than that observed in 36 fetuses with trisomy 21 (56%) at the same gestational age [11].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our findings are consistent with those of postnatal échocardio graphie studies in affected neonates and post mortem studies of stillbirths or postnatal deaths (table 2) [1][2][3][4]. The frequency of septal defects (84%) was higher than that observed in 36 fetuses with trisomy 21 (56%) at the same gestational age [11].…”
Section: Discussionsupporting
confidence: 82%
“…The two echocardiographic studies on tri somy 18 neonates [1,2] reported that in the majority of cases the valvular abnormalities were of no haemodynamic significance. This may offer an explanation for the lack of an obvious association between the overall inci dence of valvular abnormalities and the de gree of nuchal oedema.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its frequency in postmortem (autopsy) and in vivo (echocardiographic) series has been similar and ranged from 45 to 100% (usually above 90%) [Hodes et al, 1978;Moerman et al, 1982;Kinoshita et al, 1989;Balderston et al, 1990;Musewe et al, 1990;Embleton et al, 1996;Niedrist et al, 2006;Pont et al, 2006]. In our study the frequency was in the high side of the range (97%).…”
Section: To the Editorsupporting
confidence: 60%
“…CHD is present in more than 90% of all infants with trisomy 18, including VSD and patent ductus arteriosus (PDA). Karyotype analysis is necessary for a definitive diagnosis; however, the presence of polyvalvular disease is a useful adjunct to other clinical assessments [Balderston et al, 1990]. CHD is present in almost 80% of infants with trisomy 13 [Polli et al, 2014].…”
Section: Aneuploidies and Chdmentioning
confidence: 99%